Formulating an organizational pride model for the National Iranian Oil Company - Seyed Mostafa Seyedpour; Ali Safari; Ali Nasr Isfahani (Cogent Business & Management, 2020)
The present study addresses the formulation of organizational pride model in the National Iranian Oil Company (NIOC). Exploratory mixed method was used in this study, of which the first phase was conducted using grounded theory. Participants of the qualitative phase of the study constituted 19 managers, directors, supervisors, and experts of the NIOC, whose interviews were analyzed to extract and formulate the desired model in the form of causative relations. Then, the findings of the qualitative phase were formulated in the form of statements, which were put to test in the quantitative phase. In line with this, a researcher-made questionnaire was administered to 381 employees of the NIOC. Upon ensuring the validity and reliability of the instrument, structural equation modeling (SEM) was used to calculate the results of the fit indicators. This model constitutes causative conditions (intrinsic motivation, sense of national pride, successful background of the organization, organizational image, and importance of the organization's output), central phenomenon (emotional organizational pride and attitudinal organizational pride), Context (Political-legal factors, Sociocultural factors, Economic-technological factors), intervening conditions (supervisor consideration, perceived organizational justice, welfare and financial facilities, and transparency of career path), strategies (positive views about the entirety of the organization, extra-organizational positive views, job enthusiasm, employees and their families' prejudice to the organization, and commitment to the organization's values) and consequences (organizational identity, retention in the organization, organizational citizenship behavior, and employees' performance enhancement). In addition, the results of the quantitative phase confirm the hypotheses and support the findings of the qualitative phase.
Keywords: 650; organizational pride; emotional organizational pride; attitudinal organizational pride; National Iranian Oil Company (NIOC); grounded theory